The association between an established Chief Experience Officer role and hospital patient experience scores - William Breen; Seongwon Choi; Kristina "Ria" Hearld; Stephen O'Connor; Edward Rafalski; Nancy Borkowski (The Beryl Institute, 2021)
The healthcare industry is currently reacting to multiple stakeholders demanding improvements to the patient experience. Some healthcare organizations are implementing new management structures, i.e., the role of Chief Experience Officer (CXO). This study statistically reviewed descriptors associated with hospitals that have and have not created and filled the role of CXO and, more importantly, measured the association between the CXO role and results of patients' perceptions of their experience of care as measured by publicly reported Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) results. This study was conducted utilizing data gather on hospitals in three states, California, Florida, and New York. The results of the study yield insight into the organization characteristics of hospitals and the market factors associated with those hospitals that have filled the CXO role. Hospitals with a formal CXO role are larger, more likely to be for profit, and operate in metro areas of these states with higher per capita income. In addition, hospitals that have a formal CXO role are also more likely to have higher HCAHPS scores as determined by the patient recommendation question as well as the hospital overall rating question included in the HCAHPS survey. Experience Framework This article is associated with the Culture & Leadership lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Culture%20%26%20Leadership%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens